CORRELATION OF OWNERSHIP STRUCTURE AND FIRM PERFORMANCE - Ong, Khar Kuan Alex (2008)
Family controlled businesses control a fairly high percentage of economy in any place of the world. The main objective of this management project assignment is to investigate the relation between ownership structure and firm performance in Singapore, using data from fifteen public traded corporations that is listed in Singapore Exchange Ltd. Although family-controlled corporations exhibit larger separation between control and cash-flow rights, I would like to find out whether family control hampers firm performance and in what way will it affect the company.